Port Site Infections Following Laparoscopic Cholecystectomy - Siddiqua, Sadia Sajmin; Khan, Md Azizul Islam; Khan, Md Arif Uddin; Sayeed, Shovon (Bangladesh Journal of Medicine, 2018)
Background: Port site infections (PSIs) following laparoscopic cholecystectomy is an infrequent complication. Among the causes of PSIs Mycobacterium tuberculosis is rare but it has been increasingly recognized in the recent years. Lack of awareness of this complication leads to prolonged morbidity. Early diagnosis and treatment is important for theresolution of the disease. Methods: This was an observational descriptive study carried out on patients who underwent laparoscopic cholecystectomy. In patients of PSIs, Gram and AFB staining with culture & sensitivity of pus and biopsy of abscess wall or sinus tract were obtained as per need to reach the diagnosis. Patients were treated accordingly. Results: The rate of PSIs was 3.92% in this study. Age, sex & body weight have no impact on PSIs. Diabetes mellitus, hypertension, hypothyroidism, acute cholecystitis & spillage of bile or stone during the procedure increases the rate of PSIs. Epigastric port was affected more than that of other ports. Among the causes of port site infections in 55.18% cases it was with Gram +ve bacteria, in 34.49% cases with Gram -ve bacteria, in 1.72% cases atypical mycobacteria, in 5.17% cases Mycobacterium tuberculosis & in 3.44% cases no organisms were found. Most of the PSIs developed early within one month & responded well with antibiotics. Diagnosisof port site tuberculosis was established by histopathological examination of tissue from abscess wall or sinus tract & treated as per WHO guide line. No recurrence noted at 2 years follow up. Conclusion: Port site tuberculosis after laparoscopic cholecystectomy is a rare entity. The present study is an attempt to make surgeons aware of this rare complication. Early diagnosis and proper treatment are prerequisites to the successful outcome. Strict adherence to well established sterilization protocol is a must for the prevention. Bangladesh J Medicine Jul 2018; 29(2) : 51-58